Spacing Effect on the Percentage of Life and Growth of Rhizophora Apiculata in Mangrove Education Center Marine Station University of Riau - Arifin, Taat Mujaid; ', Efriyeldi; ', Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted in March-May 2014 in central study mangrovemarine station University Riau. This study aims to determine the effect of spacingon percentage seedling survival and growth of Rhizophora apiculata. The methodused in this research were experimental methods. Spacing treatment tested in thisstudy were: (1) Planting with a distance of 25 cm x 25 cm (2) Planting with adistance of 50 cm x 50 cm (3) Planting with a distance of 75 cm x 75 cm and (4)Planting by distance planting 100 cm x 100 cm. The results of the study for 45days was observed that the percentage of survival of the seedlings of Rhizophoraapiculata in various types of treatment spacing of the percentage of live 100%.Seedling height growth of Rhizophora apiculata good are at a spacing of 75 cm x75 cm (treatment C3) with average growth height of 0.080 cm/day. Meanwhile,the best steam diameter growth is best on Rhizophora apiculata are at a spacing of25 cm x 25 cm (treatment A2), with a trunk diameter growth of 0.0030 cm / day.The highest growth the number of leaves on the seedlings reached 4.9 strandscontained in a spacing of 25 cm x 25 cm (treatment A1). The data showed thatthere was effect of spacing on height growth, diameter growth and number ofleaves on Rhizophora apiculata seedlings, while the Anova test obtained therewas no the significant effect of spacing (Sig. > 0.05). It means that the proposedhypothesis (Ho) is accepted and (Ha) was rejected, which indicates that theprovision of spacing did not significantly affect height growth, diameter growthand number of leaves on Rhizophora apiculata seedlings during the observation.Keywords: Marine station, Rhizophora apiculata, The Effect of Spacing.1). Student